The Aristocats - Clemmons, Larry 1906-1988; Hibler, Winston (Burbank, CA Distributed by Walt Disney Studios Home Entertainment, 2008)
In the heart of Paris, a kind and eccentric millionairess wills her entire estate to Duchess, her high-society cat. Duchess has three little kittens. A greedy, bumbling butler pulls off the ultimate catnap caper. Now it's up to the rough-and-tumble alley cat, Thomas O'Malley, and his band of swingin' jazz cats to save the day
Originally released as a motion picture in 1970
Title from container
1
Keywords: Butlers -- France -- Paris -- Juvenile films; Cats -- France -- Paris -- Juvenile films; Inheritance and succession -- France -- Paris -- Juvenile films; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs